Detection of long repeat expansions from PCR-free whole-genome sequence data - Mc Laughlin, Russell; Hardiman, Orla (My University, 2017)
Identifying large expansions of short tandem repeats (STRs), such as those that cause amyotrophic lateral sclerosis (ALS) andfragile X syndrome, is challenging for short-read whole-genome sequencing (WGS) data. A solution to this problem is animportant step toward integrating WGS into precision medicine. We developed a software tool called ExpansionHunter that,using PCR-free WGS short-read data, can genotype repeats at the locus of interest, even if the expanded repeat is larger thanthe read length. We applied our algorithm to WGS data from 3001 ALS patients who have been tested for the presence oftheC9orf72repeat expansion with repeat-primed PCR (RP-PCR). Compared against this truth data, ExpansionHunter cor-rectly classified all (212/212, 95% CI [0.98, 1.00]) of the expanded samples as either expansions (208) or potential expansions(4). Additionally, 99.9% (2786/2789, 95% CI [0.997, 1.00]) of the wild-type samples were correctly classified as wild typeby this method with the remaining three samples identified as possible expansions. We further applied our algorithm to a setof 152 samples in which every sample had one of eight different pathogenic repeat expansions, including those associatedwith fragile X syndrome, Friedreich’s ataxia, and Huntington’s disease, and correctly flagged all but one of the known repeatexpansions. Thus, ExpansionHunter can be used to accurately detect known pathogenic repeat expansions and provides re-searchers with a tool that can be used to identify new pathogenic repeat expansion
PUBLISHED
Keywords: Short tandem repeats (STRs); Amyotrophic lateral sclerosis (ALS); Fragile X syndrome; Whole-genome sequencing (WGS) data; Software tools; ExpansionHunter